Imagining Home in Diaspora in Leila S. Chudori’s Pulang (Home) - Retno Wulandari (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
Diaspora literature has been one of literary genres that is flourishing for the last few years in Indonesia. This paper aims at analyzing the concept of home in diaspora in Leila S. Chudori’s Pulang (Home). The novel is about the experience of Indonesian exile in 1960s in French, in which he and his friends cannot return home due to the accusation of their involvement in Indonesian banned party. Through sociological approach, the concept of home by Mallet and Golob are used to explore this literary work. A close reading method and classification based on the topic are used in researching the novel. The result shows that although the main character experiences marginalization and estrangement, he still wants to return to Indonesia. The concept of home for the main character is not about the movement or created in the new land, but home is where one originates and that is a place to return.Keywords:diaspora, home